Analysis and mitigation of SSR in non-identical generators using multimodal BPF based SSDC. (January 2022) - Venkateswarlu, S.; Janaki, M.; Thirumalaivasan, R.
Abstract: The multimodal non-identical generators having close frequency modes may complicate the design of subsynchronous damping controller. In this paper, the Band-Pass Filter (BPF) based Subsynchronous Damping Controller (SSDC) is designed with SSSC to damp multimode SSR. The system is adapted from IEEE First Benchmark Model (FBM) with two non-identical generators in parallel. One of the generators has a six-mass mechanical system and other has a four-mass mechanical system. The SSDC using reduced number of BPFs is proposed to enhance the damping of multimodal SSR while maintaining the frequency selectivity of filters. The proposed BPF based SSDC is designed to modulate the SSSC injected voltage so as to suppress the multimode components in the line. The DQ model is developed in MATLAB-Simulink using the differential and algebraic equations of the combined system. The analysis of SSR are carried out through damping torque, eigenvalue and transient simulation. The participation factor analysis is performed to identify the torsional modes of the generators. The eigenvalue analysis is used to select the number of BPFs. The BPFs with appropriate frequency selectivity are chosen to improve the damping of all critical torsional modes in the entire range of practical compensation level. The results show that, the peak negative damping at both generators is considerably reduced with the proposed SSDC in the entire range of torsional mode frequencies through practical compensation levels. Highlights: Modeling of power system with multimachines in DQ reference frame. Different methods to analyze SSR. Design of robust Subsynchronous Damping Controller (SSDC) for non-identical machines with reduced number of Band Pass Filters (BPF). Validation of effectiveness of the robust BPF based SSDC. SSR characteristics with hybrid compensation incorporating SSSC and BPF based SSDC.